New trends in sport science—observations from the 30th Annual Congress of the European College of Sport Science in Rimini - Raastad, T.; Ferrauti, A.; Jones, A. M.; Thompson, J. L. (European Journal of Sport Science, 2026)
The Annual Congress of the European College of Sport Science (ECSS), this year held in Rimini, Italy, gives a yearly indication on new trends on hot topics within the field of sport science. Unter the evocative theme "Sport Science from Renaissance to the Millenial Era", the congress brought together over 3000 delegates from across the glove, celebrating both the historical roots and future directions of the discipline.